2021
DOI: 10.20289/zfdergi.694965
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cumin essential oil on the fermentation quality, aerobic stability, and in vitro digestibility of vetch-oat silages

Abstract: The effect of cumin essential oil on the fermentation quality, aerobic stability, and in vitro digestibility of vetch-oat silages Kimyon uçucu yağının fiğ-yulaf silajlarının fermantasyon kalitesi, aerobik stabilitesi ve in vitro sindirilebilirlik üzerine etkisi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…x FOR PEER REVIEW 3 of 14 branched-chain volatile fatty acids (BCVFA), ratio acetate to propionate (C2:C3), dry matter digestibility (DMD), and organic matter digestibility (OMD). [20] 2018 Alfalfa Cumin 300-500 Akinci and Onenc [21] 2021 Vetch-oat Cumin 200-500 Junior et al [22] 2019 Sugarcane Lemongrass 1000-3000 Duru [23] 2020 Alfalfa Lavender flower 5-20 Soycan-Onec et al [24] 2015 Field pea Origanum, Cinnamon, Mix (Origanum and Cinnamon) 400 Li et al [25] 2022 Mulberry Amomum villosum 5 Besharati et al [26] 2022 Alfalfa and apple pulp Mix (ricinoleic acid, cardol, cardanol) 500 Vaičiulien ė et al [27] 2022 Perennial ryegrass, Red clover, and Blue alfalfa Oregano and Thymol 20…”
Section: Database Developmentmentioning
confidence: 99%
“…x FOR PEER REVIEW 3 of 14 branched-chain volatile fatty acids (BCVFA), ratio acetate to propionate (C2:C3), dry matter digestibility (DMD), and organic matter digestibility (OMD). [20] 2018 Alfalfa Cumin 300-500 Akinci and Onenc [21] 2021 Vetch-oat Cumin 200-500 Junior et al [22] 2019 Sugarcane Lemongrass 1000-3000 Duru [23] 2020 Alfalfa Lavender flower 5-20 Soycan-Onec et al [24] 2015 Field pea Origanum, Cinnamon, Mix (Origanum and Cinnamon) 400 Li et al [25] 2022 Mulberry Amomum villosum 5 Besharati et al [26] 2022 Alfalfa and apple pulp Mix (ricinoleic acid, cardol, cardanol) 500 Vaičiulien ė et al [27] 2022 Perennial ryegrass, Red clover, and Blue alfalfa Oregano and Thymol 20…”
Section: Database Developmentmentioning
confidence: 99%
“…Chaves et al [11] stated that the use of cinnamon extract at low levels was able to reduce the content of NDF and ADF. Meanwhile, the use of essential oil from cumin was able to reduce cellulose and ADF but had no effect on ADL and hemicellulose [12]. Silage fermentation quality parameters, in which several parameters prove that the use of essential oils effects the decrease in several parameters of fermentability and organic acid content such as LA, acetic acid, and propionic acid.…”
Section: Resultsmentioning
confidence: 97%
“…The use of essential oils as a silage additive can indirectly reduce nutrient loss during silage. After adding 200 mg/kg of cumin (C. cyminum) essential oil, the colony structure of wild oat silage changes considerably, and the lactic acid bacteria multiply in large quantities to produce acid, reduce the pH value, and then inhibit the activity of protein degradation enzymes, thereby reducing the degradation of proteins (Akinci and Önenc, 2021). In addition, the results showed that plant oils directly inhibit the activity of bacterial amylases and proteases.…”
Section: Improving the Feeding Quality Of Silagementioning
confidence: 99%